Spatiotemporal evolution and driving factors of green energy efficiency in Jiangsu Province: a sustainable development perspective - Zhang, Xin; Wang, Han; Jiang, Songyu (Frontiers in Environmental Science, 2025)
With the ongoing global climate change and energy structure transformation, green energy efficiency has become one of the key indicators for achieving sustainable development. This study uses panel data from 13 prefecture-level cities in Jiangsu Province, China, from 2012 to 2022 to explore the spatiotemporal evolution and driving factors of green energy efficiency. The study employs the super-efficiency Slack-Based Measure (SBM) method to measure the green energy efficiency of each region. It uses the Gini coefficient and kernel density estimation methods to analyze the spatiotemporal evolution characteristics of green energy efficiency. Furthermore, based on a fixed effects model, the study delves into the main driving factors influencing green energy efficiency. The results show that green energy efficiency in Jiangsu Province is generally on an upward trend. The Gini coefficients of both the southern and northern regions of Jiangsu have increased, but the gap in green energy efficiency between the two regions has gradually widened. The degree of government intervention and the level of industrialization are unfavorable to the growth of green energy efficiency. In contrast, foreign investment levels, financial development, and urbanization show significant positive effects. Finally, based on the empirical findings, targeted recommendations are provided to promote green energy efficiency, offering important theoretical support and empirical evidence for the country’s strategic goals of achieving green and low-carbon development.